Al‐Doped ZnO Nanowires by Electrochemical Deposition for Selective VOC Nanosensor and Nanophotodetector. Issue 16 (25th April 2018) - Pauporté, Thierry; Lupan, Oleg; Postica, Vasile; Hoppe, Mathias; Chow, Lee; Adelung, Rainer
Abstract : Nanomaterials for new nanosensor systems with selective detection of hazardous volatile organic compounds (VOCs) vapors are of great demand nowadays. In this paper, the use in nanosensors of electrochemically deposited (ECD) Al‐doped ZnO (ZnO:Al) nanowires (NWs) is reported. The NWs are characterized by micro‐Raman and optical measurements. Individual ZnO and ZnO:Al NWs are integrated into nanosensor devices for room temperature UV and gas sensing. It is shown that, compared to undoped ZnO NW with irreversible response, the doped ZnO:Al NWs have faster response (≈5 s) and recovery (≈55 s), as well as enhanced UV response (≈4.8, about 2 times higher). The room temperature gas sensing investigations demonstrate that an individual ZnO:Al NW can detect volatile organic compounds (VOCs) vapors such as 2‐propanol, n ‐butanol and ethanol at room temperature with a relatively fast response time of ≈10 s and a reversible signal (the recovery time being 30–40 s). This shows the possibility to use it with further development as indoor air quality monitor. Abstract : The improved UV sensing performances of an individual ZnO:Al nanowire with a radius of 125 nm compared to an undoped ZnO nanowires (NWs) is reported in this work. The ZnO:Al NW shows also excellent room temperature sensing properties for selective detection of volatile organic compounds vapors.